A comparative cross-sectional study on the prevalence of psychiatry disorder, substance misuse and neurotic personality traits between male sexual offenders and non sexual offenders in Pokok Sena prison - Karim, Idyawati Abdul (2010)
To determine the prevalence and association of psychiatry disorder, substance misuse and neurotic personality traits with sexual offending behaviours in male sexual offenders and non sexual offenders in Pokok Sena Prison, Kedah. This cross-sectional study was conducted in Pokok Sena Prison, Kedah. Study population consisted of one hundred and forty ( 140) offenders who had been convicted and was undergoing their sentence in Pokok Sena Prison from June 2010 to July 2010. Seventy (70) participants were selected from the sexual offenders' group and another seventy (70) participants from the non sexual offenders' group. The participants were interviewed using a constructed Clinical Data Form (CDF) for sociodemographic data, clinical and criminal history. They were also assessed for psychiatry morbidity using the Structured Clinical Interview for DSM-IV Axis I Diagnosis: Clinician Version (SCID-1-CV, First et.al, 1997). MHQ was used to screen for neurotic personality traits. Statistical analyses were performed by SPSS version 17.0. Majority of the population study sample was Malays and Muslims. Mean age for sexual offenders was in the mid thirties, have a lower educational level and earning less than RM I 000 per month. There was a significant difference found in terms of family history of psychiatric illness and family history of substance misuse. Sexual offenders also had a higher proportion of parental separation before the age of 16 years old and history of both parents working compared to the non sexual offenders. For the related criminal record, past history of sexual crimes was found to be higher in the sexual offenders' group. On the whole, there is no significant difference in psychiatric diagnosis between the two groups. However, there was a significant difference in psychotic and mood disorder when individually diagnosed between sexual and non sexual offenders. There was also a significant difference found in the presence of substance disorder between the two groups. In terms of personality assessment, the subscale for somatic anxiety was significantly higher in the sexual offender group. There were significant differences found in some of the factors in the sociodemographic data, clinical and criminal history. No significant differences found in psychiatric diagnosis as a whole. However, there was a significant difference in terms of psychotic and mood disorder diagnosed, presence of substance disorder and higher proportionate of somatic anxiety personality in the sexual offender group.